101 GLYCEMIC, LIPID, AND ANTHROPOMETRIC MEASURES IN ELDERLY SOUTH ASIAN INDIAN IMMIGRANTS. (1st January 2005) - Rosewater, I. G.; Caputo, D.; Parikh, S.; Farooki, A.; Amorosa, L. F.
Abstract : We obtained data in a population of South Asian Indian immigrants with male predominance, as compared to South Asian Indians in the US census 2000 New Jersey data. The table displays glucose, lipid and body mass measures of age matched males (n = 63) and females (n = 44) older than 58 years old. Due to this population's high mean FSG, the cohort was further stratified into glycemic groups: N = (FSG < 100 mg/dL and A1C < 6.4%); I = (FSG ≥ 100 and < 126 and A1C < 6.4); D = (FSG ≥ 126 and A1 ≥ 6.4). FSG across all glycemic groups correlated with the A1C, r = .77 (p < .01). All body mass and lipid measures were compared in men and women within the glycemic groups as illustrated by the data for HDL, triglycerides and weight shown in the figures below. Of the lipid measures, only HDL differed between sexes (F = 10.4, .002) and between all glycemic groups for each sex (men F = 5.6, .006) and (women F = 5.0, .052). The change in HDL correlated negatively with weight in men (r = -.49, p < .01) but not in women. Weight correlated with waist circumference in both men (r = .79) and women (r = .43), p < .01 for each. HDL did not correlate with waist/hip in either sex. Triglycerides correlated to HDL (r = -.35, r = -.57), p < .01 for both men and women respectively.